The Effect of Project-based Learning on Self-efficacy and Learning Outcomes of Physics Students in High School on Momentum and Impulse Learning Material - M. Rizki Febrian; Bambang Supriadi; Firda Kusuma Ayu Anggraeni (Universitas Lambung Mangkurat, 2026)
Physics learning at the high school level is typically characterized by a predominance of teacher-led activities over student engagement, resulting in suboptimal student confidence and learning outcomes. This study aims to examine the effect of the application of the project-based learning (PjBL) learning model on student learning outcomes, especially in the learning material of momentum and impulse. This study is based on the need for innovative transformation of learning management to improve the quality of human resources and the active involvement of students as learning subjects. The employed research method is quantitative with a control-only design. The research sample comprised 10th-grade science students at Ibrahimy High School, categorized into Science 1 as the experimental group employing the project-based learning model and Science 2 as the control group utilizing the conventional model. The homogeneity test yielded a significance value of 0.620, which exceeds 0.05, indicating that the pre-test data for both the experimental and control classes are homogeneous. The normality test of the self-efficacy questionnaire data was conducted on 31 data samples using the Shapiro-Wilk method. The questionnaire and post-test normality test demonstrated that the data distribution in both the experimental and control groups was normal. The t-test on the questionnaire scores revealed a significance value of 0.002, which is below 0.05, indicating that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. Thus, there was a significant difference in self-efficacy between students in the experimental class and the control class. Moreover, the t-test on the post-test scores showed a significance value of 0.000, less than 0.05, meaning that (Ho) was rejected and (Ha) was accepted. Thus, the learning outcomes between both classes were significantly different. This study concludes that the implementation of the project-based learning model significantly enhances student self-efficacy and learning outcomes in comparison to conventional learning models. PjBL has demonstrated the capacity to foster more dynamic and solution-focused learning via real-world problem-solving and innovative product development.